2010
DOI: 10.1182/blood-2009-10-247510
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of allogeneic hematopoietic stem cells for adult T-cell leukemia: a nationwide retrospective study

Abstract: Allogeneic hematopoietic stem cell transplantation (HSCT) is increasingly used as a curative option for adult T-cell leukemia (ATL), an intractable mature T-cell neoplasm causally linked with human T-cell leukemia virus type I (HTLV-I). We com-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
208
4
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(235 citation statements)
references
References 42 publications
12
208
4
6
Order By: Relevance
“…Antibody-based approaches including use of daclizumab, alemtuzumab, and anti-CCR4 showed value but are not curative (31)(32)(33)(34). Allogeneic bone marrow transplantation is an aggressive approach that is curative in select patients (35). Due to these limited options, there is a clear need for new treatment strategies for ATL.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody-based approaches including use of daclizumab, alemtuzumab, and anti-CCR4 showed value but are not curative (31)(32)(33)(34). Allogeneic bone marrow transplantation is an aggressive approach that is curative in select patients (35). Due to these limited options, there is a clear need for new treatment strategies for ATL.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a large retrospective study was reported in 2010 and included 386 patients allografted between 1995 and 2005 using either standard or reduced-intensity conditioning regimens. 18 After a median follow-up of 41 months, the 3-year OS was 33%. Interestingly, donor HTLV-I seropositivity adversely affected the disease-associated mortality, specifically for patients who received transplants from related donors.…”
mentioning
confidence: 97%
“…This may be due to poorer outcome of CBT than BMT/PBSCT in ATL patients than other diseases. 19 Alternately, it may be associated with a small size of the subgroup. Therefore, these observations should be confirmed in a prospective analysis of larger numbers of patients.…”
Section: Discussionmentioning
confidence: 99%